Rancang Bangun Prototype Dongkrak Mekanik Dengan Media Komunikasi Smartphone - Aripin Triyanto; Ariyawan Sunardi; Ojak Abdul Rozak; Rendra Sasmita (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
A mechanical jack is one of the tools that is needed for every vehicle owner, especially in car workshops. Smartphone is a modern communication tool and the most widely used today. Some individuals or institution also have to take advantage of technological developments to make work more effective, efficient, and safer. For example, in operating a mechanical jack, although it looks simple, it requires time and energy to operate it. Therefore, a prototype of a mechanical jack controller was made by maximizing the Smartphone as an interface that is connected to the NodeMCU ESP8266 Microcontroller via the internet network which can later be developed in its actual form. The method used is to program NodeMCU for DC motors, current sensors, load cells, with the aim that the jack can be controlled remotely and the current on the DC motor and the load on the jack can be monitored via a smartphone. The results obtained from the study are, the jack can increase and decrease the maximum load of 5kg, with a current when rising is 0.31A, and the average time to rise is 42 seconds. With the effectiveness of the working distance between the jack and the smartphone can be controlled remotely.